Basin analysis and sequence stratigraphy a review, with a short account of its applicability and utility for the exploration of auriferous placers in the Witwatersrand Basin - Van Eeden, Johan (Rhodes University, Faculty of Science, Department of Geology, 1996)
The Witwatersrand basin is unique in terms of its mineral wealth. The gold in the Witwatersrand basin is mainly concentrated in the placers and two types of unconformities are associated with the placer formation. This paper attempts to quantitatively describe the origin and depositional process of placers within the context of basin analysis, geohistory and sequences stratigraphic framework. Several tectonic models have been proposed for the evolution of the Witwater~rand basin and it seems as if a cratonic foreland basin accounts for many of the observed features observed the Central Rand Group basin. The tectonic subsidence curve generated for the Witwatersrand Basin clearly implies foreland basin response which was superimposed an older, deep seated extensional basin. These compressive tectonics can be superimposed on extensional basins, where the shift from extensional to compressional tectonics lead to inversion processes. The critical issues about the Witwatersrand basin which were addresed in this review, is the validity of basin wide correlation of placer unconformuties and whether sequence stratigraphy is applicable to fluvial systems of the Witwatersrand sequence. It is believed that the Central Rand Group was deposited as alluvial - fan deltas by fluvially dominated, braidplain systems with minor marine interaction which had a considerable impact on the preservation of economically viable placers. Most important to the exploration geologist is the recognition of stacking patterns of the fluvial strata to determine change in the rate at which accommodation was created. Identifying sequence boundaries and other relevant surfaces important for identifying these stacking patterns of the sequences, depends entirely on the recognition of a hierarchy of stratal units including beds, bedsets, parasequences, parasequence sets and the surfaces bounding sequences. Placers are closely associated with the development of disconformities and therefore become important to recognise in fluvial strata. If these placers are to become economic, the duration of subaerial exposure of the unconformities that allowed the placers to become reworked and concentrated must be determined. In order to preserve the placer, a sudden marine transgression is necessary to allow for minimal shoreline reworking and to cap the placer to prevent it from being dispersed. The placers in the Witwatersrand basin occur in four major gold-bearing placer zones in the Central Rand Group. Accordingly they can be assigned to four supercycles, which are cyclical and therefore predictive. It is the predictive nature of these rocks and the ability of sequence stratigraphy to enhance this aspect, which is a pre-requisite for an effective exploration tool in the search for new ore bodies or their extension in the Witwatersrand basin.
Keywords: Geology, Stratigraphic; Sedimentary basins -- South Africa; Placer deposits -- South Africa